Mapping the land movement level of Langsa Baro district using the Geographic Information System (GIS) - Riyan, Muhammad Alfriyandi; Ellida Novita Lydia; Eka Mutia; Arisna Fauzia (Teknisia, 2025)
Langsa Baro District is an area that often experiences floods and a lot of uneven elevation in the area so that land movement can be possible. This study aims to analyze the parameters that affect soil movement and make a zoning map of the level of vulnerability of land movement using spatial data in Langsa Baro District. Data processing with GIS (Geographic Information System) is intended to obtain soil movement mapping. To help determine the weight score on each parameter, this study used the AHP (Analytic Hierarchy Process) method. Factors that greatly influence the occurrence of soil movement that occurs in Langsa Baro District are soil type and rainfall. The Langsa Baro District area has five levels of vulnerability, namely the level of vulnerability of very low soil movement with a percentage of 0.26% and area of 17.02 Ha, the level of vulnerability of low soil movement with a percentage of 3.58% and an area of 234.02 Ha, the level of vulnerability of medium soil movement with a percentage of 18.42% and an area of 1204.22 Ha, the level of vulnerability of high soil movement with a percentage of 73.74% and an area of 4819.54, the level of vulnerability of soil movement is very high with a percentage of 4.00% and an area of 261.26 Ha.